PENETAPAN KADAR PARACETAMOL PADA OBAT MIRASIC MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI (KCKT) - Ryan Ramadhan; M.Mahfudz Faudzi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Cases of paracetamol overdose in Indonesia are still difficult to identify comprehensively. In 2023, the Analysis Study of Drug and Food Poisoning Cases conducted by the Indonesian Food and Drug Authority (BPOM) reported 463 cases (26.89%) of poisoning caused by drugs. Paracetamol overdose is a condition of paracetamol poisoning caused by the use or consumption of paracetamol exceeding the recommended therapeutic dose; therefore, calculating the amount of dose consumed is an important initial step in diagnosis. A pharmaceutical preparation can achieve good quality and the desired therapeutic effect if the drug meets the quality requirements stated in the Indonesian Pharmacopoeia or other standard references using the High Performance Liquid Chromatography (HPLC) method. The results of the study showed that the average level of paracetamol in the sample was 96.7%. According to the Indonesian Pharmacopoeia Sixth Edition, the acceptable range for paracetamol content is 90%–110%, indicating that the sample met the Pharmacopoeia requirements.